The use of orthophoto map for soils mapping of dwindling lakes catchment areas: a case study of Sumowskie Lake, NE Poland - Mendyk, Łukasz; Markiewicz, Maciej; Świtoniak, Marcin; Bednarek, Renata (Ecological Questions, 2013)
The aim of the study was to assess the suitability of aerial photos for mapping the soils of dwindling lakes catchment areas. The study area is located in the North Poland, within the Brodnica Lakeland and it includes the direct catchment area of dwindling Sumowskie Lakes. There were three test area established for soil mapping. The photointerpretation was based on both immediate properties (colour of topsoil) for ploughed cultivated fields, and intermediate properties (vegetation and relief) for the areas of forests, shrubs or permanent pasture. The obtained results confirm the high usability of the cartographic materials such as aerial photographs and topographic maps for studies on specifications of areas such as the vicinities of dwindling lakes.